Clinical Course and Treatment Implications of Combination Immune Checkpoint Inhibitor-Mediated Hepatitis: A Multicentre Cohort. Issue 1 (28th July 2021) - Smith, Matthew K; Chan, Yin; Suo, Aleksi E; Shaheen, Abdel Aziz; Congly, Stephen E; Tandon, Puneeta; Bhanji, Rahima A; Wells, Malcolm M; Cheng, Tina; Ma, Christopher
Abstract: Background: Immune-related adverse events can occur after treatment with immune checkpoint inhibitors (ICI), limiting treatment persistence. We aimed to evaluate the clinical course of ICI-mediated hepatitis (IMH) associated with combination ipilimumab and nivolumab treatment. Methods: A retrospective cohort study including consecutive patients with metastatic melanoma treated with ipilimumab and nivolumab between 2013 and 2018 was conducted at two tertiary care centres. IMH was defined by the Common Terminology Criteria for Adverse Events (CTCAE). We determined the proportion of patients developing IMH, and compared the duration, treatment patterns and outcomes, stratified by hepatitis severity. Kaplan–Meier survival analysis was used to evaluate time to hepatitis resolution, and a linear mixed-effects model was used to compare longitudinal outcomes by treatment. Results: A total of 63 patients were included. Thirty-two patients (51%) developed IMH (34% Grade 1–2, 66% Grade 3–4), at a median of 34 days (IQR 20 to 43.5 days) after the first dose. Baseline FIB4 index ≥1.45 was associated with IMH (OR 3.71 [95% CI: 1.03 to 13.38], P = 0.04). Ninety-four per cent (30/32) of patients had liver enzyme normalization after a median duration of 43 days (IQR 26 to 70 days). Corticosteroid use was not associated with faster IMH resolution or less ICI discontinuation. A total of 24 patients died during the study; no deaths were attributable to hepatitis-related complications. Fifty-three per cent (17/32) of patients resumed anti-PD-1 monotherapy and three patients developed IMH recurrence. Conclusions: Approximately half of the patients treated with combination ipilimumab and nivolumab developed IMH in this cohort. However, most patients experienced uncomplicated IMH resolution.